2012
DOI: 10.1371/journal.pone.0045993
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of Breast Cancer-Associated Genes by Progesterone Receptor Isoforms PRA and PRB in a New Bi-Inducible Breast Cancer Cell Line

Abstract: Progesterone receptor isoforms (PRA and PRB) are expressed at equal levels in normal mammary cells. However, alteration in PRA/PRB expression is often observed in aggressive breast cancer suggesting differential contribution of PR isoforms in carcinogenesis. The mechanisms underlying such processes remain to be established mainly due to paucity of appropriate cellular models. To investigate the role of PR isoforms and the impact of imbalanced PRA/PRB ratio in transcriptional regulation, we have generated an or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
43
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 85 publications
9
43
0
Order By: Relevance
“…The progesterone-activated cPR-B stimulated the expression of FKBP5, SGK, and MT1 although to a much lower extent than hPR-B and hBUS did. With the exception of FKBP5 all other genes are regulated in a modified T47D human breast cancer cells also when only the PR-A isoform is expressed [49] in line with the idea that there may be some crosstalk of the overexpressed cPR-B with PR-A regulated gene expression.…”
Section: Discussionsupporting
confidence: 68%
“…The progesterone-activated cPR-B stimulated the expression of FKBP5, SGK, and MT1 although to a much lower extent than hPR-B and hBUS did. With the exception of FKBP5 all other genes are regulated in a modified T47D human breast cancer cells also when only the PR-A isoform is expressed [49] in line with the idea that there may be some crosstalk of the overexpressed cPR-B with PR-A regulated gene expression.…”
Section: Discussionsupporting
confidence: 68%
“…The nPRB/nPRA ratio determines the response of the tissue to P4 agonists or antagonists [22]. Disturbed isoform balance or overexpression of one of them could contribute to the development of carcinomas in mammary glands, ovary and endometrium, or correlate with tumor progression into more aggressive forms [24].…”
Section: Genomic Pathwaymentioning
confidence: 99%
“…PNET cases with markedly increased PR expression were reported to be significantly associated with better disease-free survival [9] , suggesting PR to be a potential prognostic marker in PNET. However, the status of PR isoform expression has not been investigated in PNET, and therefore it is not known which PR isoform plays the functional role of progesterone in NET mentioned above, since a higher ratio of PRA to PRB was reported to influence the clinical outcome in breast [12] and endometrial cancer patients [14] . The results of our in vitro experiment indicated that PRB was the only isoform expressed in the NET cell lines examined in this study.…”
Section: Immunohistochemical Evaluation Of the Pr Isoforms And Ccnd1 mentioning
confidence: 99%
“…In humans, PR exists in two isoforms, PRA and PRB [12,13] , but the exact difference between these two isoforms has not been fully clarified in NET. The results of the present study revealed that PRA was more frequent than PRB in PNETs and that PRA immunoreactivity plays an inhibitory role in cell proliferation.…”
Section: Immunohistochemical Evaluation Of the Pr Isoforms And Ccnd1 mentioning
confidence: 99%
See 1 more Smart Citation